Effect of Prior Sternotomy on Outcomes in Transvenous Lead Extraction. (September 2019) - Tsang, Darren C.; Perez, Adryan A.; Boyle, Thomas A.; Carrillo, Roger G.
Abstract : Background: A history of open-heart surgery has been a heavily debated topic in transvenous lead extraction. This study evaluates the impact of prior sternotomy on transvenous lead extraction outcomes. Methods: Data for all patients undergoing transvenous lead extraction at a tertiary referral center were prospectively gathered from 2004 to 2017. Relevant clinical information was compared between patients with a history of sternotomy before transvenous lead extraction and those without. After considering baseline differences, multivariate regression, and propensity-matched analysis were performed. Outcome variables included major and minor complication rates, clinical success, and in-hospital mortality as defined by the 2017 Heart Rhythm Society consensus statement. Results: Of 1480 patients in the study period, 455 had a prior sternotomy. When compared with patients with no prior sternotomy, those with prior sternotomy were more likely to be older, male, and present with more comorbidities and leads targeted for extraction. No statistical differences were identified in major and minor complication rates ( P =0.75, P =0.41), clinical success rate ( P =0.26), and in-hospital mortality ( P =0.08). In patients with prior sternotomy, there were no instances of pericardial effusion after extraction. Prior sternotomy was not an independent predictor of clinical or procedural outcomes. No associations were elucidated after propensity-matched analysis. Conclusions: In a large, single-center series, no differences in clinical or procedural outcomes were elucidated between patients with a history of sternotomy and those without. Patients with sternotomies before lead extraction who experienced vascular or cardiac perforations clinically presented with hemothoraces rather than pericardial effusions.